Anchorage of Au3+ into Modified Isoreticular Metal–Organic Framework-3 as a Heterogeneous Catalyst for the Synthesis of Propargylamines. Issue 1 (December 2017) - Liu, Lili; Tai, Xishi; Zhou, Xiaojing; Xin, Chunling; Yan, Yongmei
Abstract Postsynthetic modification of metal-organic framework is a general and practical approach to access MOF-based catalysts bearing multiple active sites. The isoreticular metal–organic framework-3 (IRMOF-3) was modified with lactic acid through condensation reaction of the carboxyl group of lactic acid and amino group present in IRMOF-3 frameworks. Au3+ was subsequently anchored onto the metal–organic framework IRMOF-3 using postsynthetic modification. The synthezized IRMOF-3-LA-Au (LA = lactic acid) was characterized by powder X-ray diffraction, N2 adsorption-desorption, infrared spectroscopy, liquid-state nuclear magnetic resonance, thermogravimetric analysis, H2 -temperature programmed reduction, transmission electro microscopy, and inductively coupled plasma–optical emission spectrometry. IRMOF-3-LA-Au acted as an efficient heterogeneous catalyst in the synthesis of propargylamines by three-component coupling reaction of aldehyde, alkyne, and amine. Moreover, the catalyst is applicable to various substituted substrates, including aromatic and aliphatic aldehydes, alkyl- and aryl-substituted terminal alkynes, and alicyclic amines. In addition, the catalyst can be easily separated from the mixture and can be reused for four consecutive cycles.